The Influence of Military Defensive Factor on the Process of Establishing Russia’s Southern Frontier in the XVI-XIX Centuries - Elena V. Linkova; Dmitry E. Evsyukov (RUDN Journal of Russian History)
The authors examine the evolution of the main ideas and concepts explaining the territorial expansion of the Russian state and analyzes their applicability to substantiating the advancement of the borders of the Russian state southward in historical retrospect of the XVI-XIX centuries. Based on the concept of natural boundaries and the theory of the frontier, the main stages of by the Russian state in establishing its southern border are analyzed within the text. It is noted that at all stages of its statehood, in fact, Russia adhered to the defensive doctrine of foreign policy, and the process of expanding the territory southward was associated with the consistent construction of defensive lines. By the XVI-XVII centuries with the help of those defensive lines, the Russian state claimed its rights to these lands as the legal successor of Kievan Rus. The feature of the following centuries was the construction of fortified lines to protect the borders established as a result of ongoing warfare, and their construction was enshrined in international treaties. The process of Russia's movement southward was completed upon reaching the natural boundaries of the Black Sea coast, which made it possible to ensure the safety of the territories and the population of the southern frontier.